2004
DOI: 10.1002/cbdv.200490056
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Ibogan and Vallesamine Derivatives from Tabernaemontana divaricata

Abstract: Six new indole alkaloids, viz., (3S)-3-cyanocoronaridine (2), (3S)-3-cyanoisovoacangine (3), conolobine A (5), conolobine B (6), conolidine (7), and (3R/3S)-3-ethoxyvoacangine (8), in addition to 36 known ones, were obtained from the stem-bark extract of the Malayan Tabernaemontana divaricata. The structures were determined by NMR and MS analysis. The CN-substituted alkaloids showed appreciable cytotoxicity towards the KB human oral epidermoid carcinoma cell-line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 36 publications
2
51
0
Order By: Relevance
“…Kam, Loh, and Wei () isolated conophylline (5) and conophyllidine (6) as two new dimeric indole alkaloids with a yield of 3.5 mg/kg from it. Recently, Kam, Pang, Choo, and Komiyama () evaluated a total of 42 different types of bioactive alkaloids from Tabernaemontana divaricata with new ibogan (Conolabines A and B; 15 ) and vallesamine alkaloid (16) derivatives. Low et al () reported Lirofoline B (7) as a new pentacyclic indole alkaloid in its stem bark with a yield of 3.2 mg/kg.…”
Section: Phytochemistrymentioning
confidence: 99%
“…Kam, Loh, and Wei () isolated conophylline (5) and conophyllidine (6) as two new dimeric indole alkaloids with a yield of 3.5 mg/kg from it. Recently, Kam, Pang, Choo, and Komiyama () evaluated a total of 42 different types of bioactive alkaloids from Tabernaemontana divaricata with new ibogan (Conolabines A and B; 15 ) and vallesamine alkaloid (16) derivatives. Low et al () reported Lirofoline B (7) as a new pentacyclic indole alkaloid in its stem bark with a yield of 3.2 mg/kg.…”
Section: Phytochemistrymentioning
confidence: 99%
“…This was further substantiated by the characteristic long-range W-couplings (ca. 2.5 Hz) observed between H(17a)/H(15a), H(17b)/H(3b), H(15b)/H (21), and H(15b)/H(3a), which are characteristic of the 2-aza-bicyclo[2.2.2]octane unit associated with an iboga ring system. The major fragments revealed, which are the 10-methoxy-indole and the 2-aza-6-ethylbicyclo[2.2.2]octane units, are also found in ibogaine (3, Scheme 1), indicating a close similarity between the two structures.…”
Section: Introductionmentioning
confidence: 95%
“…10 The Malayan representatives of this genus are also notable for producing new indole and bisindole alkaloids, including a number which exhibited important biological activities. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] We now report the isolation and structure elucidation of two new pentacyclic indole alkaloids, lirofolines A (1) and B (2), from the stem-bark extracts of T. corymbosa and T. divaricata, respectively. 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Voacangine has been isolated from T. iboga root bark (Dickel et al, 1958) and reportedly inhibits AChE at the same concentration as the reference compounds physostigmine and galantamine (Andrade et al, 2005). Ibogaine co-occurs with voacangine in T. divaricata (Kam et al, 2004), a species that produces particularly strong AChE inhibition among plants used in Thai traditional medicine (Ingkaninan et al, 2003), and other alkaloid and non-alkaloid constituents of T. divaricata that could inhibit AChE (Chattipakorn et al, 2007) might possibly co-occur with ibogaine in T. iboga as well.…”
Section: Resultsmentioning
confidence: 99%